2001
DOI: 10.1017/s0954394501131042
|View full text |Cite
|
Sign up to set email alerts
|

Phrase-level parallelism effect on noun phrase number agreement

Abstract: Linguistic parallelism (i.e., the tendency of similar forms to occur together within a stretch of discourse) has been shown to be very strong in many linguistic phenomena and in a vast number of languages. Examining the role of phrase-level parallelism on noun phrase number agreement, this article demonstrates that Puerto Rican Spanish and Brazilian Portuguese exhibit more similarities than differences with regard to this constraint. A detailed analysis of Brazilian Portuguese data is presented, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 1 publication
(2 reference statements)
5
45
0
3
Order By: Relevance
“…Furthermore, subjects without a plural marker on the last element tend to trigger unmarked plural verbs. These effects have been described in detail in the relevant literature on Brazilian Portuguese for the last 30 years, in articles published in Language (Naro 1981), Language Variation and Change (Scherre and Naro 1991, 1992, Naro and Scherre 1996a, Scherre 2001) and in Selected Papers from NWAV 8 (Scherre 1981, Guy 1981, NWAV 23 (Naro and Scherre 1996b), NWAV 38 (Scherre and Naro 2010).…”
Section: Nonstandard Constructions Cited In the Textbookmentioning
confidence: 99%
“…Furthermore, subjects without a plural marker on the last element tend to trigger unmarked plural verbs. These effects have been described in detail in the relevant literature on Brazilian Portuguese for the last 30 years, in articles published in Language (Naro 1981), Language Variation and Change (Scherre and Naro 1991, 1992, Naro and Scherre 1996a, Scherre 2001) and in Selected Papers from NWAV 8 (Scherre 1981, Guy 1981, NWAV 23 (Naro and Scherre 1996b), NWAV 38 (Scherre and Naro 2010).…”
Section: Nonstandard Constructions Cited In the Textbookmentioning
confidence: 99%
“…Um outro procedimento tradicional nos estudos sobre a variação PL no SN no PB é a análise do efeito da presença de outras marcas de PL no SN, anteriores ao item em análise (SCHERRE, 1988(SCHERRE, , 1989(SCHERRE, , 2001). Esses estudos encontram uma maior probabilidade de marcação de PL nos itens precedidos de outros itens com marca de PL.…”
Section: O Efeito Da Presença De Marcas Precedentes Sobre a Marcação unclassified
“…These studies have demonstrated linear parallel effects on the marking of plural /-s/: strings such as SS__ favor a following plural marker, while combinations such as SØ__ favor a missing /-s/ (Scherre, 1998a(Scherre, , 1998b(Scherre, , 1998c(Scherre, , 2001Scherre & Naro, 1991, 1998. In Misiones Portuguese rates of depleted plural marking are so high as to be nearly categorical, as shown in Table 1.…”
Section: Depleted Plural Marking In Vernacular Brazilian and Misionesmentioning
confidence: 99%